EXPLORING ANATOMICAL VARIATIONS OF RENAL ARTERIES THROUGH CADAVERIC STUDY, BIHAR, INDIA: A CROSS-SECTIONAL STUDY. - Singh, Divyanjali; Rani, Sweta; Ranjan, Rakesh (Student’s Journal of Health Research Africa, 2024)
Background The anatomical variations of the renal artery are of paramount importance in medical sciences, impacting surgical interventions, diagnostic imaging, and the understanding of renal pathologies. This study aims to document the variations in renal artery anatomy through cadaveric dissection, shedding light on their clinical implications. Methods A cross-sectional study was conducted involving 100 cadavers. Cadavers with intact renal arterial anatomy were included, while those with major congenital anomalies or damage were excluded. Standard dissection protocols were followed to observe and document variations in the renal arteries, including number, course, origin, and morphology. Results The demographic analysis of the 100 cadavers (55% male and 45% female) revealed a mean age of 67 years (± 8.2), indicating a broad age spectrum. Anatomical variations in the renal arteries were identified in 78 cadavers, showcasing a diverse range of alterations from the typical arterial anatomy. The study’s detailed dissection process uncovered a notable prevalence of accessory renal arteries in 42% of the cases, with these arteries predominantly originating from the abdominal aorta (60%). Other origins included the inferior mesenteric artery (25%) and the common iliac artery (15%). The branching pattern analysis further highlighted a trifurcation pattern in 18% of the cases, contrasting with the more commonly observed bifurcation pattern in 62%. Conclusion The high prevalence of renal artery variations underscores the necessity for detailed anatomical knowledge among clinicians and surgeons to navigate these differences effectively during surgical and diagnostic procedures. Recommendations Further studies are recommended to explore the clinical implications of these variations in renal artery anatomy, particularly in the context of renal surgeries and interventions. Enhanced imaging techniques should be developed to better identify and characterize these variations preoperatively.